HIPERTENSI PADA ANAK: TINJAUAN PUSTAKA - Pratama, Radya Putra; Alexandra, Florence; Saad, Nursan (Medical and Health Journal, 2024)
Hypertension in the pediatric population is a serious health problem that needs attention. Although the incidence is not as high as in adults, pediatric hypertension can increase the risk of cardiovascular and kidney disease later in life. This article aims to review the definition, epidemiology, etiology, pathogenesis, clinical manifestations, diagnosis, and management of pediatric hypertension. The causes of hypertension in the pediatric population can be divided into primary hypertension, which is generally associated with obesity and metabolic syndrome, and secondary hypertension, which is most often caused by kidney disorders. The diagnosis of pediatric hypertension is established through history taking, physical examination, and investigations. Management of pediatric hypertension includes lifestyle modifications and administration of antihypertensive drugs, depending on the severity and presence of target organ damage. Regular blood pressure checks after the age of 3 years are important so that pediatric hypertension can be detected and treated early to prevent long-term complications.